Formalization of wastepickers in Bogota and Lima: Recognize, regulate, and then integrate? - Mélanie Rateau; Luisa Tovar (EchoGéo)
Waste management models in Colombia and Peru are at a turning point in favor of the integration of informal waste pickers. The Capital District of Bogota and Lima's fifty municipalities are putting in place formalization processes that are more than just a formality. It involves recognizing, regulating and integrating wastepickers. The study of the processes at work in these two cities reveals distinct models of formalization with contrasting impacts on the informality and the marginality of a practice and the population dedicated to it.